Breaking A World War I (WWI) Story from The Characters’ Point of View in Film “1917” - Fitriyah, Fitriyah; Mizola Revanza, Mario; Alawiyah, Sufi (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
A movie, also known as a film or motion picture, is a form of visual art used to entertain audience that can communicate ideas, stories, perceptions, feelings, or atmosphere through moving images. The aims of the research are to analyze the world war I story from the main character point of view from “1917”. This thesis aims to show readers how frightening war can be and how it differs from what is portrayed in the media. In order to gather information for this thesis, two ideas from Postcolonial Theory and Characterization as well as the movie "1917" are used. To elaborate on this concept, the writers employs a descriptive qualitative method. The results shows that there are six characters in the movie “1917”. First, he is Lance Corporal Schofield who is the one who going through a lot throughout the film. He experiences mental breakdown, anger, stress and exhaust. Second, Lance Corporal Blake, he has the heroic traits. Third, General Erinmore, a man who shows how orders can be crucial. Fourth, Lieutenant Leslie who shows how war can give sadness, stress and care with each other. Fifth, Colonel Mackenzie also shows how order really crucial in short time. And the last, Lieutenant Joseph Blake, he shows how heartbreaking in World War I when the closes one died, it gives pain, sadness, and stress.